PENGARUH SERVANT LEADERSHIP DAN WORKPLACE SPIRITUALITY TERHADAP TURNOVER INTENTION GURU DI SEKOLAH XYZ BATAM MELALUI ORGANIZATIONAL CITIZENSHIP BEHAVIOR SEBAGAI VARIABEL MEDIASI - Rita Kristina; Niko Sudibjo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The high turnover rate among teachers can negatively impact the quality of education in schools. Servant leadership and workplace spirituality are considered important factors that can enhance teachers' commitment and job satisfaction, thereby potentially reducing their intention to leave the organization. Additionally, organizational citizenship behavior (OCB) is thought to strengthen the relationship between servant leadership and workplace spirituality in the workplace, fostering an intention to remain with the organization. This study aims to determine whether servant leadership and workplace spirituality influence teachers' turnover intention and to explore the mediating role of OCB in this relationship. Data were collected through a survey by distributing questionnaires to 74 teachers at XYZ School in Batam and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that servant leadership and workplace spirituality have a positive influence on OCB but servant leadership do not directly affect turnover intention. Contrarily, workplace spirituality was found to have a negative impact on turnover intention. OCB does not mediate between servant leadership, workplace spirituality, and turnover intention.